Konsep Manusia Menurut Suku Dayak Jalai Dalam Cahaya Filsafat Ernst Cassirer - Riyant, Petrus; Melania, Tabita (IKIP PGRI Pontianak, 2024)
The research focuses on exploring and excavating the concept of the Dayak Jalai people according to the philosophy of Ernst Cassirer, with data collection and exploration centered on the Dayak Jalai people, Jelai Hulu District, Ketapang Regency, West Kalimantan, aiming to unearth and document the values of local wisdom specifically regarding the concept of humans as animal symbolicum, employing qualitative methodology through literature studies and analysis of existing data, while also ensuring the authenticity of writings about the traditions of the Dayak Jalai people through in-depth interviews with six informants, revealing that the concept of humans as animal symbolicum advocated by Ernst Cassirer permeates into the life and culture of the Dayak Jalai people, with similarities between the thoughts of Ernst Cassirer and the Jalai people lying in the discovery of the concept of symbols, which distinguishes humans from other animals.